2011
DOI: 10.3109/02699052.2010.541897
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Post-Concussion Assessment and Cognitive Testing battery and traditional neuropsychological measures: A construct and concurrent validity study

Abstract: While both batteries overlap regarding their assessed constructs (e.g. memory, inhibitory cognitive abilities) notable differences in their factor structures were present as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 25 publications
1
57
0
Order By: Relevance
“…The authors found that ImPACT and traditional tests overlapped regarding constructs such as speed or cognitive efficiency and memory, but had notable differences in certain constructs such as in auditory and verbal working memory and inhibitory cognitive abilities. 67 Overall, correlational analyses in that study provided support for the ImPACT battery's validity in assessing memory and cognitive efficiency in a healthy volunteer cohort. Based on the aforementioned data, owing to differences between tests, and in the absence of any one superior computerised test, it is recommended that the same test be used on any given player from pre-injury (baseline) testing through to post-injury follow-up.…”
Section: Neuropsychological Testingmentioning
confidence: 65%
See 2 more Smart Citations
“…The authors found that ImPACT and traditional tests overlapped regarding constructs such as speed or cognitive efficiency and memory, but had notable differences in certain constructs such as in auditory and verbal working memory and inhibitory cognitive abilities. 67 Overall, correlational analyses in that study provided support for the ImPACT battery's validity in assessing memory and cognitive efficiency in a healthy volunteer cohort. Based on the aforementioned data, owing to differences between tests, and in the absence of any one superior computerised test, it is recommended that the same test be used on any given player from pre-injury (baseline) testing through to post-injury follow-up.…”
Section: Neuropsychological Testingmentioning
confidence: 65%
“…67 The CogSport test consists of eight tasks designed as card games which, in about the same overall timeframe, assess reaction time, matching, monitoring and learning tasks in a language-independent manner. 68 Using ImPACT, Fazio et al 56 found that athletes who denied having any symptoms of concussion in the first few days following a concussive injury performed significantly worse across a number of ImPACT's neurocognitive composite scores compared to a matched control group.…”
Section: Neuropsychological Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Schatz 10 investigated ImPACT reliability over a 2-year span and found degradation of these values, reporting ICCs of 0.46, 0.65, 0.74, and 0.68 for verbal memory, visual memory, visual motor speed, and reaction time, respectively. In both baseline and postconcussion settings, 1,11,12 ImPACT has been validated against other neuropsychological measures and was shown to be approximately 90% sensitive and 70% specific in detecting cognitive dysfunction and diagnosing concussion, 3,13 even in the absence of reported symptoms. 13,14 However, other investigators have shown poor to moderate reliability, 6,15 low sensitivity, 6 and a high (30%) false-positive rate.…”
mentioning
confidence: 99%
“…Computerized neurocognitive tests are relatively quick and yield specific domains that may be altered with concussion (e.g., reaction time, verbal memory, and mental processing speed) (12). Recent concussion consensus statements (3,13) have deemed neurocognitive testing to be an objective indicator of concussion recovery.…”
mentioning
confidence: 99%